A Practical Guide to the Management of the Fetus and Newborn With Hemophilia. (December 2018) - Moorehead, Paul C.; Chan, Anthony K. C.; Lemyre, Brigitte; Winikoff, Rochelle; Scott, Heather; Hawes, Sue Ann; Shroff, Manohar; Thomas, Aidan; Price, Victoria E.
Newborns with hemophilia are at risk of intracranial hemorrhage, extracranial hemorrhage, and other bleeding complications. The safe delivery of a healthy newborn with hemophilia is a complex process that can begin even before conception, and continues throughout pregnancy, birth, and the newborn period. This process involves the expectant parents and a wide variety of health-care professionals: genetic counselors, obstetricians, neonatologists, pediatricians, radiologists, adult and pediatric hematologists, and nurses with expertise in hemophilia. Because of this multidisciplinary complexity, the relative rarity of births of newborns with hemophilia, and the lack of high-quality evidence to inform decisions, there is considerable variation in practice in this area. We present a comprehensive multidisciplinary approach, from preconception counseling to discharge planning after birth, and describe available options for management decisions. We highlight a number of areas of important uncertainty and controversy, including the preferred mode of delivery, the appropriate use and timing of neuroimaging tests, and the appropriate use of clotting factor concentrates in the newborn period. While the approach presented here will aid clinicians in planning and providing care, further research is required to optimize the care of newborns with hemophilia.